2015
DOI: 10.1111/jfs.12159
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Effects of Ozonated Water on Aspergillus parasiticus: A New Approach to Prevent Wheat Contamination

Abstract: In Iran, wheat is one of the most important sources of diet. Unfortunately, it is vulnerable to contamination with fungi consisting of aflatoxigenic moulds. Since 1997, ozone has been recognized as an effective oxidant and disinfection agent. This study demonstrates the benefits derived from ozone in the inhibition of Aspergillus parasiticus growth and aflatoxin production in wheat. Wheat samples inoculated with A. parasiticus spore suspensions (10,10 2 and 10 4 spores/g of wheat) were treated with ozonated wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…The same effects of O 3 have been studied by other authors using different ozonation conditions in wheat samples, which demonstrate that O 3 is also effective for the control of Fusarium graminearum and Penicillium citrinum (Savi and Scussel ), Aspergillus parasiti cus (Mohammadi Kouchesfahani et al . ), A. flavus and P. citr iunum (Savi et al . ) and also for reduction on total fungal count (Zhao et al .…”
Section: Discussionmentioning
confidence: 99%
“…The same effects of O 3 have been studied by other authors using different ozonation conditions in wheat samples, which demonstrate that O 3 is also effective for the control of Fusarium graminearum and Penicillium citrinum (Savi and Scussel ), Aspergillus parasiti cus (Mohammadi Kouchesfahani et al . ), A. flavus and P. citr iunum (Savi et al . ) and also for reduction on total fungal count (Zhao et al .…”
Section: Discussionmentioning
confidence: 99%
“…The efficiency of an ozone decontamination method depends on the type of treatment, type of food, temperature, pH, and contact time. Ozone treatment has been used on different types of food (Akbas & Ozdemir, 2008;Asokapandian et al, 2018;Concha-Meyer, Eifert, Williams, Marcy, & Welbaum, 2015;Doane & Johnson, 2018;Gonçalves, 2009;Mohammadi Kouchesfahani et al, 2015;Niemira, 2012;Trombete, Freitas-Silva, Saldanha, Venâncio, & Fraga, 2016Xu, 1999). Studies showed that ozonization, exposing food to O 3 gas, can reduce the viability of bacterial and fungal contaminants and reduce microbial metabolite accumulation (Freitas-Silva & Venâncio, 2010).…”
Section: Chemical Detoxification Methodsmentioning
confidence: 99%
“…[15] The ozonized water also can be used in cereals, like wheat grains, that need to go through a moisture step before milling. [16] The main reasons for applying O 3 in wheat grain are for pest and insect control, [17] elimination of fungi, [18] degradation of mycotoxin, [19,20] and degradation of pesticide residues. [21,22] As O 3 does not leave any residues in the treated food, there is no need for an aeration step after treatment, and also due to the excellent results of ozonation, it has been considered a "green alternative" to improve wheat quality.…”
Section: Introductionmentioning
confidence: 99%